1999
DOI: 10.1016/s0014-5793(99)01521-5
|View full text |Cite
|
Sign up to set email alerts
|

Induced expression of adipophilin mRNA in human macrophages stimulated with oxidized low‐density lipoprotein and in atherosclerotic lesions

Abstract: Oxidized low-density lipoprotein (OxLDL) plays a critical role in foam cell formation and atherosclerogenesis. A cDNA encoding adipophilin was identified in cultured human macrophages stimulated with OxLDL using mRNA differential display. Adipophilin is a 50 kDa protein known to be a specific marker for adipocyte cell differentiation and lipid accumulation in a variety of cells. The time-dependent induction of adipophilin mRNA in macrophages was specific to OxLDL but not native LDL, and not to various cytokine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
75
0
2

Year Published

2000
2000
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(84 citation statements)
references
References 23 publications
(31 reference statements)
7
75
0
2
Order By: Relevance
“…Adipophilin, the only gene up-regulated at 2.5 h, is a known marker for Most Highly Regulated Genes-A list of the 10 most highly up-regulated genes (Table I) shows that eight of these genes are most up-regulated at day 4. This group includes three genes that have previously been shown to be responsive to Ox-LDL loading of macrophages in culture and/or to appear in foam cell-rich regions of plaque tissue: adipophilin, heparin-binding epidermal growth factor-like growth factor (HB-EGF), and thrombomodulin (23)(24)(25). These latter findings help validate the THP-1 cell model and the microarray procedures.…”
Section: Resultsmentioning
confidence: 99%
“…Adipophilin, the only gene up-regulated at 2.5 h, is a known marker for Most Highly Regulated Genes-A list of the 10 most highly up-regulated genes (Table I) shows that eight of these genes are most up-regulated at day 4. This group includes three genes that have previously been shown to be responsive to Ox-LDL loading of macrophages in culture and/or to appear in foam cell-rich regions of plaque tissue: adipophilin, heparin-binding epidermal growth factor-like growth factor (HB-EGF), and thrombomodulin (23)(24)(25). These latter findings help validate the THP-1 cell model and the microarray procedures.…”
Section: Resultsmentioning
confidence: 99%
“…ADFP is an ϳ50 kDa protein that is highly expressed as adipocytes differentiate into mature adipocytes (48), as well as in monocytes (27) and macrophages (49), and belongs to the perilipin family of lipid storage proteins (50). Immunofluorescence staining has shown that ADFP coats the cytosolic surface of intracellular neutral lipid droplets (51).…”
Section: Discussionmentioning
confidence: 99%
“…Examination of a variety of tissue culture cells also has revealed ADRP as a ubiquitous component of lipid droplets (6,15). Moreover, enhanced expression of ADRP is a useful marker for pathologies that are characterized by increased accumulations of lipid droplets (6,(21)(22)(23)(24). Hence, analysis of ADRP would provide valuable insight into the nature of proteins that associate with lipid droplets.…”
mentioning
confidence: 99%